Los organizadores gráficos como recurso didáctico para la enseñanza-aprendizaje de Biología Vegetal con los estudiantes de tercer semestre de la carrera de Pedagogía de las Ciencias Experimentales Química y Biología”, periodo octubre 2020 –marzo 2021 - Caranqui Yaguarshungo, Silvia Nataly (2021)
In order to successfully execute the pedagogical process of Plant Biology, it is essential to use resources that, in addition to adapting to technological advances, provide active participation for the benefit of reasoning and creativity, such as visual schemes. However, in the Pedagogy of Experimental Sciences career Chemistry and Biology, its application is scarce and limited because the students are unaware of the use and management of the different schemes applied to carry out learning. For this reason, the use of graphic organizers is proposed as a didactic resource for the teaching-learning process of Plant Biology through the design of a curricular instructional guide to correctly structure the different techniques in the curricular topics of the subject since the adequate elaboration of graphic organizers demonstrate the development of cognitive competences. The methodology used according to the research context is non-experimental, bibliographic, and field, using the inductive-deductive and analysis-synthesis methods. In order to attach the required information, a survey was conducted for the 42 apprentices in Plant Biology. The analyzed data shows that there is great interest on the part of the students, since 92% mention being willing to use different visual techniques due to the benefits that favor the construction of knowledge through active learning where the educational environment becomes interesting, creative, and entertaining in such a way that the student is thoughtful, critical and capable of solving their learning needs.